HUBUNGAN PERAN KADER DAN DUKUNGAN KELUARGA DENGAN KELENGKAPAN IMUNISASI DASAR PADA BAYI DI WILAYAH KERJA PUSKESMAS TARUSAN - Sri Oktarina (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The primary immunization complete if infants receive fifth types of immunization ( HB - 0, BCG, Polio vaccine, DPT / HB, measles vaccine) and the amount of the provision is complete. The completeness of primary immunization at district of Puskesmas Tarusan is 73.47 % with a target of 90% in 2015. The purpose of this study is to determine the factors that related with the completeness of primary immunization in infants at district Puskesmas Tarusan 2016. The type of research is descriptive analytic with Cross Sectional approach . This research is conducted in two Kenagarian at District Puskesmas Tarusan, Pesisir Selatan September 2015 until June 2016. The population in this study are all mothers who have children aged 1-3 years. The samples in this study as many as 80 people and samples are taken by random sampling propotionate . Data analyzed by univariate and bivariate with Chi - Square test. The results of univariate analysis showed that ( 63.8 % ) provision of basic immunization in infants is incomplete , 38 % of families are less supportive in providing complete primary immunization, 56 % less cadre role in the provision of complete primary immunization. The results of the bivariate analysis showed significant relationship between family support, and the role of cadres with a completeness primary immunization in infants at district of Puskesmas Tarusan. Suggested to the holders of the mother and child of health program can increase the coverage of completeness primary immunization in infants, the cadres expected to provide information to mothers about complete primary immunization, and expected to the holders of health promotions program and mother and child of health programs can often provide training to the cadres. Keywords: primary immunization